Smallholder shallow groundwater irrigation development in the upper east region of Ghana - Namara, Regassa E.; Awuni, J.A.; Barry, Boubacar; Giordano, Mark; Hope, Lesley; Owusu, Eric S.; Forkuor, Gerald (International Water Management Institute, 2011)
In Sub-Saharan Africa, there is paucity of information on the potential of groundwater resources. The limited available information paints a pessimistic view about groundwater resources. Due to its perceived inadequate availability, groundwater associated with domestic use and the potential for using it for agriculture are not well reflected in the national irrigation polices. Contrary to official pessimism, farmers do use groundwater for agriculture in many countries of Sub-Saharan Africa including Ghana. This paper analyzes the current extent of use, economics, socioeconomic impacts, and constraints and opportunities of shallow groundwater irrigation based on the experiences of smallholders in the three micro-watersheds of the White Volta Basin in the Upper East Region of Ghana.